2021
DOI: 10.3390/ijms22094422
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HR Repair as a Synthetic Lethal Approach to Increase DNA Damage Sensitivity by a RAD52 Inhibitor in BRCA2-Deficient Cancer Cells

Abstract: BRCA mutation, one of the most common types of mutations in breast and ovarian cancer, has been suggested to be synthetically lethal with depletion of RAD52. Pharmacologically inhibiting RAD52 specifically eradicates BRCA-deficient cancer cells. In this study, we demonstrated that curcumin, a plant polyphenol, sensitizes BRCA2-deficient cells to CPT-11 by impairing RAD52 recombinase in MCF7 cells. More specifically, in MCF7-siBRCA2 cells, curcumin reduced homologous recombination, resulting in tumor growth sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The molecular targets of the active metabolite of irinotecan, SN-38, are Top1-DNA covalent reaction intermediates that are reversibly stabilized by SN-38 and result in DNA strand breaks [Figure 5] [28] . DNA damage by irinotecan has been documented in regards to an increase in DNA damage by the inhibition of proteins, such as Rad51 and Rad52, which are involved in DNA repair.…”
Section: Changes In Drug Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular targets of the active metabolite of irinotecan, SN-38, are Top1-DNA covalent reaction intermediates that are reversibly stabilized by SN-38 and result in DNA strand breaks [Figure 5] [28] . DNA damage by irinotecan has been documented in regards to an increase in DNA damage by the inhibition of proteins, such as Rad51 and Rad52, which are involved in DNA repair.…”
Section: Changes In Drug Targetsmentioning
confidence: 99%
“…DNA damage by irinotecan has been documented in regards to an increase in DNA damage by the inhibition of proteins, such as Rad51 and Rad52, which are involved in DNA repair. Curcumin was reported to target homologous recombination through the inhibition of Rad52, resulting in the sensitization of irinotecan-inducing DNA damage [ 29 ] . Flavopiridol, a cyclin-dependent kinase inhibitor, was shown to be beneficial to patients with advanced solid tumors that expressed wild-type p53 treated with irinotecan through the suppression of Rad51 [ 30 ] .…”
Section: Mechanisms Of Irinotecan Refractorinessmentioning
confidence: 99%
“…Hendriks et al [ 55 ] demonstrated that curcumin was able to prevent the SUMOylation of histone H3. Also, more recently, it was shown to block the SUMOylation of RAD52, a protein important for DNA double-strand break repair [ 56 ]. Being SUMOylation activated and influenced by oxidative stress [ 13 ], these results, together with our previous findings, indicate that Curcuma could act as a SUMOylation inhibitor with both direct inhibiting protein SUMOylation and indirect inhibiting oxidative stress mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The docking analysis of EGFR L858R/T790M/C797S (PDB ID: 6LUB) and of the EGFR wild‐type apo structure (PDB ID: 5FED) with psorachromene was performed using BIOVIA Discovery Studio software, version 19.1.0.18287, as described previously (Tseng et al, 2021).…”
Section: Methodsmentioning
confidence: 99%